RESPON BEBERAPA VARIETAS TANAMAN PARE (Momordica charantia L.) TERHADAP APLIKASI DOSIS PUPUK HAYATI - Wahyuningsih, Titin Ambarwati; Ihsan, Mohammad; Widiastuti, Libria (Agros Journal of Agriculture Science, 2024)
The bitter melon plant is a plant that is very suitable for planting in lowland areas, such as moorlands or yard areas. This research was carried out in Dukuh Blasinan, Desa Kaligawe, Kec.Pedan Kab. Klaten, Prov. Jawa Tengah. This research used a Complete Randomized Block Design (RAKL) with 6 treatment combinations, namely: V₁ P₁ = combination of Lipa F1 plant variety and biofertilizer dose of 2.25 g/plant, V₁ P₂ = combination of Lipa F1 plant variety and biofertilizer dose of 3g/plant , V₁ P₃ = combination of Lipa F1 plant variety and biofertilizer dose of 3.75 g/plant, V₂ P₁ = combination of Raden F1 plant variety and biofertilizer dose of 2.25 g/plant, V₂ P₂ = combination of Raden F1 plant variety and fertilizer dose biological 3g/plant, and V₂ P₃ = combination of the Raden F1 plant variety and biological fertilizer dose of 3.75 g/plant. These observation parameters include: plant height (cm), number of fruit per plant (fruit), fruit weight per plant (grams), average fruit length per plant (cm), weight of fresh plant stover (grams) . The research results showed that the dose of Petrobio biological fertilizer affected the parameters of plant height, number of fruit per plant, weight of fruit per plant, average length of fruit per plant, and weight of fresh plant stover. The best yield of the bitter melon variety is Lipa F1 and the best fertilizer dose is 3.75 grams/plant. Keywords: Bitter Melon, Biological Fertilizer, Varieties INTISARITanaman pare merupakan tanaman yang sangat cocok ditanam didaerah dataran rendah, seperti tegalan atau lahan pekarangan. Penelitian ini dilaksanakan di Dukuh Blasinan, Desa Kaligawe, Kec.Pedan Kab. Klaten, Prov. Jawa Tengah. Penelitiaan ini menggunakan Rancangan Acak Kelompok Lengkap (RAKL) dengan 6 kombinasi perlakuan, yakni : V₁ P₁ = kombinasi varietas tanaman Lipa F1 dan dosis pupuk hayati 2,25 g/tanaman, V₁ P₂ = kombinasi varietas tanaman Lipa F1 dan dosis pupuk hayati 3g/tanaman, V₁ P₃ = kombinasi varietas tanaman Lipa F1 dan dosis pupuk hayati 3,75 g/tanaman, V₂ P₁ = kombinasi varietas tanaman Raden F1 dan dosis pupuk hayati 2,25 g/tanaman, V₂ P₂ = kombinasi varietas tanaman Raden F1 dan dosis pupuk hayati 3g/tanaman, dan V₂ P₃ = kombinasi varietas tanaman Raden F1 dan dosis pupuk hayati 3,75 g/tanaman. Parameter pengamatan ini meliputi : tinggi tanaman (cm), jumlah buah per tanaman (buah), berat buah per tanaman (gram), rata-rata panjang buah per tanaman (cm), berat brangkasan segar tanaman (gram). Hasil Penelitian menunjukkan bahwa pemberian dosis pupuk hayati petrobio berpengaruh terhadap parameter tinggi tanaman, jumlah buah per tanaman, berat buah per tanaman, rata-rata panjang buah per tanaman, dan berat brangkasan segar tanaman. Hasil terbaik varietas pare yaitu Lipa F1 dan dosis pupuk terbaik yaitu 3,75 gram/tanaman. Kata Kunci: Pare, Pupuk Hayati, Varietas